Meaning, medicine, and merit - Mogensen, A (Cambridge University Press, 2019)
Given the inevitability of scarcity, should public institutions ration healthcare resources so as to prioritize those who contribute more to society? Intuitively, we may feel that this would be somehow inegalitarian. I argue that the egalitarian objection to prioritizing treatment on the basis of patients’ usefulness to others is best thought of as semiotic: i.e. as having to do with what this practice would mean, convey, or express about a person’s standing. I explore the implications of this conclusion when taken in conjunction with the observation that semiotic objections are generally flimsy, failing to identify anything wrong with a practice as such and having limited capacity to generalize beyond particular contexts.